Achieving homogeneity in a high-Fe β-Ti alloy laser-printed from blended elemental powders. (15th November 2021) - Ahmed, Farheen F.; Clark, Samuel J.; Alex Leung, Chu Lun; Stanger, Leigh; Willmott, Jon; Marussi, Sebastian; Honkimaki, Veijo; Haynes, Noel; Zurob, Hatem S.; Lee, P.D.; Phillion, A.B.
Graphical abstract: Highlights: In-situ alloying of a Ti-1Al-8V-5Fe powder during Selective Laser Melting was investigated using synchrotron X-ray diffraction and infra-red thermal imaging. The alloying process of a β-Ti powder was studied by X-ray diffraction and IR imaging. Exothermic mixing aids in melting but this gives a mix of alloyed & unalloyed regions A consistent microstructure is only achieved via thermal cycling in the HAZ Abstract: Blended Elemental powders are an emerging alternative to pre-alloyed powders in metal additive manufacturing due to the wider range of alloys producible with them and the cost savings from not developing novel feedstock. In this study, in situ alloying and concurrent microstructure evolution during SLM are investigated by performing SLM on a BE Ti-185 powder while tracking the surface temperatures via Infra-red imaging and phase transforma- tion via synchrotron X-ray Diffraction. We then performed post-mortem electron microscopy (Backscatter Electron imaging, Energy Dispersive X-ray Spectroscopy and Electron Backscatter Diffraction) to further gain insight into microstructure development. We show that although exothermic mixing aids the melting process, laser melting results only in a mixture of alloyed and unmixed regions. Full alloying and thus a consistent microstructure is only achieved through further thermal cycling in the heat-affected zone .